The Convergence of Legal Frameworks for Domestic & Sexual Violence: Towards Holistic Victim Protection in Indonesia - Hendro Widodo; Dzaka Imtiyaz Iqbal; Doni Catur Saefudin (Jurnal Daulat Hukum, 2026)
The protection of victims of domestic and sexual violence in Indonesia still faces serious problems due to the fragmentation of norms and procedures between the Domestic Violence Law and the Women's and Children's Protection Law, which reflect the dominance of a perpetrator-oriented criminal law paradigm and legalistic formalism. This leaves victims unpositioned as subjects who must be fully restored. The purpose of this study is to analyze a convergence model for holistic protection of victims of sexual violence. This research utilizes normative legal research with legislative, conceptual, analytical, and comparative approaches. The novelty of this research lies in the formulation of a convergence model for victim protection that conceptually integrates victim-centered justice, strengthens procedural convergence through the SPPT-PKKTP (Regional Criminal Procedure Code), adopts the principle of trauma-informed justice in criminal procedure law, and affirms the principle of non-regression in the harmonization of the National Criminal Code. victim protection stops at the substance (victim's rights) or institutional (service units), but does not lock the procedural points that make victims safe and not repeatedly injured.